Direct visualization of the thermomagnetic behavior of pseudo-single-domain magnetite particles - Almeida, Trevor P.; Muxworthy, Adrian R.; Kovacs, Andras; Williams, Wyn; Brown, Paul D.; Dunin-Borkowski, Rafal E. (American Association for the Advancement of Science, 2016)
The study of the paleomagnetic signal recorded by rocks allows scientists to understand Earth’s past magnetic field and the formation of the geodynamo. The magnetic recording fidelity of this signal is dependent on the magnetic domain state it adopts. The most prevalent example found in nature is the pseudo–single-domain (PSD) structure, yet its recording fidelity is poorly understood. Here, the thermoremanent behavior of PSD magnetite (Fe3O4) particles, which dominate the magnetic signatures of many rock lithologies, is investigated using electron holography. This study provides spatially resolved magnetic information from individual Fe3O4 grains as a function of temperature, which has been previously inaccessible. A small exemplar Fe3O4 grain (~150 nm) exhibits dynamic movement of its magnetic vortex structure above 400°C, recovering its original state upon cooling, whereas a larger exemplar Fe3O4 grain (~250 nm) is shown to retain its vortex state on heating to 550°C, close to the Curie temperature of 580°C. Hence, we demonstrate that Fe3O4 grains containing vortex structures are indeed reliable recorders of paleodirectional and paleointensity information, and the presence of PSD magnetic signals does not preclude the successful recovery of paleomagnetic signals.